Effectiveness of English Program in Teaching Speaking at LP3I Tasikmalaya Polytechnic - Yanti Fadila Wahab; Yudi Kurniadi; Ernawati Ernawati (Journal of English Language and Education, 2026)
The ability to speak English effectively is essential in global communication and professional settings. However, gaps often exist between theoretical approaches to language teaching and their practical implementation in classrooms, particularly in enhancing students’ speaking skills. Teachers frequently encounter challenges such as limited class time, large class sizes, lack of training, insufficient teaching resources, and students’ low confidence in speaking activities. Consequently, speaking instruction often remains focused on grammar exercises and textbook-based learning rather than authentic oral communication. This study aims to analyse the effectiveness of an English program in improving students’ speaking ability at LP3I Tasikmalaya Polytechnic. A qualitative case study approach was employed, involving ten students, one program coordinator, and two English teachers selected through purposive sampling. Data were collected through observations, interviews, document analysis, questionnaires, and audio-visual materials, and were analysed using data condensation, display, and conclusion drawing. The findings reveal that the English Conversation Journal (ECJ) is the most effective program in engaging students. Additionally, the program improves pronunciation, vocabulary mastery, confidence, motivation, and speaking awareness. In conclusion, the English program is effective in enhancing students’ speaking skills and supports teachers in achieving learning objectives.